The influences of macroeconomic variables towards Malaysia stock market / Muhammad Faiz Kamarudzaman - Kamarudzaman, Muhammad Faiz (2016)
Global financial crisis gives a significant impact to the rest of the countries especially developing countries like Malaysia. During financial crisis, Malaysia economy and stock market not performing well as United States economy slump to the worst financial crisis after the most worst financial crisis in history the great depression in 19th century. Global financial crisis lead to Malaysia stock index to fall and economy performance to slow down into negative economy performance. But with government initiatives and policy improvement, Malaysia economy continue to recover from the financial crisis. Hence, this study was conducted to investigation the impact of global financial crisis to the Malaysia stock market by depending on selected macroeconomic variables. For research methodology, ordinary least square (OLS) method were conducted to examine the relationship between variables. Regression analysis was used to conducted and determine the relationship with Malaysia stock market. There a few other tests such as unit root test, heteroscedasticity, Ramsey reset test and so on were conducted in this research. This study shows that all of selected macroeconomic variables that is Gross Domestic Product (GDP), Consumer Price Index (CPI), Interest Rate (IR), Oil Price (OP) and Exchange Rate (ER) are have significant relationship with the dependent variables that is Kuala Lumpur Composite Index (KLCI). The regression model also is no serial correlation model, homoscedasticity model, no multicollinearity but for Ramsey reset shows that test for the regression model is miss-specified.